Attitudes of social workers towards a task-focused model in the prevention of bedsores – A descriptive study on workers in Jazan region - 1443 AH – - Hamdhi, Ali Ahmed (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the attitudes of social workers towards the use of the task-focused model in the prevention of bedsore injuries, as well as to identify the most important skills used by social workers in dealing with this model, and the difficulties encountered in its use. It is a descriptive study whose method is a social survey. It was taken from social workers practicing their work with patients in all hospitals and health care centers in the Jazan region as a community, and allocated - using the intentional sample - a sample of (50) males and females, whose data was collected using the questionnaire tool designed by the researcher, these collected data were presented And it was analyzed through a set of descriptive and inferential statistical methods, depending on the value (0.05) as the level of statistical significance. The study reached a set of results, the most important of which are: The trends agree to the use of Model A in the prevention of bedsores injuries, and one of the most important recommendations of the study was the interest in providing more courses directed to social workers in the field of using the model, as well as interest in activating the organization of workshops for the model for specialists Social workers, while urging universities to teach the model in the departments of sociology and social work, and work to provide the possibilities to apply the model with clients, and provide the necessary equipment to use the model with bedridden clients, as well as reduce the burdens on social workers to provide them with enough time to use the task focus model.